A novel method using ambient glutamate for the electrophysiological quantification of extrasynaptic NMDA receptor function in acute brain slices - Moldavski, Alexander; Behr, Joachim; Bading, Hilmar; Bengtson, C. Peter (The journal of physiology, 2020)
We present a novel protocol to quantify extrasynaptic NMDA receptor function utilizing the semi‐selective activation of extrasynaptic receptors by ambient extracellular glutamate in acute brain slices from adult rats.